Evaluation of an examination chair to quantify the hip internal rotation angle. Issue 5 (September 2020) - Friesenbichler, Bernd; Casartelli, Nicola C; Maffiuletti, Nicola A; Leunig, Michael
Background: Deformities of the femoral head-neck junction are associated with limited hip internal rotation, which may lead to femoroacetabular impingement and consequently to hip osteoarthritis. This study compared inter- and intra-observer reproducibility of 3 different methods to quantify hip internal rotation. Methods: 2 investigators assessed hip internal rotation of 30 asymptomatic participants during 2 separate testing sessions. Internal rotation was assessed by rotating the 90°-flexed hip manually while in a supine position (manual), in an examination chair capable of applying a single load (EC1) and in a newly developed examination chair with 5 load levels (EC2). Inter- and intra-observer reproducibility was compared among methods using reliability (intra-class correlation coefficient, ICC) and measurement error (smallest detectable chance). Results: Inter-observer reliability was good for the manual assessment (ICC = 0.83) and excellent for the EC1 and EC2 methods (ICC ⩾ 0.95) with expected measurement errors of 15.9°, 7.1° and 6.8°-14.3°, respectively. Intra-observer reliability was excellent for each method (ICC ⩾ 0.96), although measurement error ranged from 7.6°-11.8° for EC2 and was slightly higher compared to the manual (7.8°) and EC1 (5.9°) methods. Conclusions: Reproducibility of EC2 hip internal rotation angle assessment is superior to that of the manual assessment at specific load levels but not to the EC1 method. Future assessment devices need to incorporate a means of precisely producing and quantifying the loads applied to the hip joint in order to improve measurement reproducibility.